Cepljenje proti človeškim papilomavirusom - Volk, Laura (Medicinski razgledi, 2022)
Human papillomaviruses (HPV) are a heterogeneous group of viruses that can cause sexu - ally transmitted diseases. HPV infections are not only associated with cervical cancer, but also with the development of anogenital warts, external genital and vaginal cancer, anal, penal, oropharyngeal cancer, and cancer of the head and neck. Most sexually active individuals become infected with HPV at least once in their lifetime. Currently, no specific treatment for HPV is available. Vaccination against HPV is currently the most successful method for preventing infection occurrence and its consequences. Countries around the world are striving to increase the HPV vaccination rate, however, it remains very low. This review addresses the current state of HPV vaccination and its strategies around the world, as well as in Slovenia.
Keywords: cepljenje; humani papiloma virus; preventiva